Microglia isolated from patients with glioma gain antitumor activities on poly (I:C) stimulation - Kees, Tim Steffen; Gdynia, Georg; Herold-Mende, Christel (Neuro-Oncology, 2012)
Abstract. The role of microglia, the brain-resident macrophages, in glioma biology is still a matter of debate. Clinical observations and in vitro studies in t